The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s00277-016-2893-6
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis in patients with a mild-to-moderate bleeding tendency of unknown cause

Abstract: In more than 50% of patients with a mild-to-moderate bleeding tendency, no underlying cause can be identified (bleeding of unknown cause, BUC). Data on parameters of fibrinolysis in BUC are scarce in the literature and reveal discrepant results. It was the aim of this study to investigate increased fibrinolysis as a possible mechanism of BUC. We included 270 patients (227 females, median age 44 years, 25–75th percentile 32–58) with BUC and 98 healthy controls (65 females, median age 47 years, 25–75thpercentile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 28 publications
(39 reference statements)
2
33
2
1
Order By: Relevance
“…Recently, an algorithm to aid in the diagnosis of patients with a bleeding tendency has been published . Three studies have demonstrated that patients with UBD have evidence of fibrionlytic abnormalities with evidence of hyperfibrinolysis and fibrinolytic regulators . This may explain the efficacy of TxA that we observed at the time of haemostatic challenges.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, an algorithm to aid in the diagnosis of patients with a bleeding tendency has been published . Three studies have demonstrated that patients with UBD have evidence of fibrionlytic abnormalities with evidence of hyperfibrinolysis and fibrinolytic regulators . This may explain the efficacy of TxA that we observed at the time of haemostatic challenges.…”
Section: Discussionmentioning
confidence: 78%
“…These high numbers underline the urgent need of studies on novel pathophysiological mechanisms to understand the bleeding tendency in these patients. In a recent study, we investigated increased fibrinolysis as a possible cause for the bleeding tendency in patients with BUC and identified a potential aetiological role of this mechanism at least in some of the patients . One hundred ninety‐six of these patients are included in the present analyses.…”
Section: Discussionmentioning
confidence: 99%
“…These include platelet storage pool diseases,29, 38 and some vWD types 39. We did not perform repeated measures, which is usually performed in the diagnostic work‐up of bleeding disorders, as many variables such as stress and circadian variation influence hemostatic measurements 7, 40, 41. Furthermore, the definition of a “hemostatic abnormality” is subject to debate.…”
Section: Discussionmentioning
confidence: 99%